PENGARUH BUDAYA ORGANISASI TERHADAP PERBEDAAN KINERJA KARYAWAN - Andi Risfan Rizaldi (Melati Institute, 2023)
This study aimed to ascertain how organizational culture influences employee performance. In addition, this study examines whether there is a distinction between the performance of male and female employees as a result of organizational culture. This study employs a quantitative approach to research design. The different test employs the independent sample T-test to determine performance differences, and a simple linear regression technique is used to determine if there are differences in the impact of organizational culture on the performance of male and female employees. Based on a different test utilizing an independent T-test, it indicates that there is a statistically significant difference between the performance of male and female employees. The results of simple linear regression indicate that organizational culture successfully influences employee performance as a whole. The regression results indicate that there is no significant difference in performance between male and female employees due to the influence of organizational culture.